VARIASI GENETIK IKAN KERAPU (Epinephelus sp) Di TPI GABION MEDAN BELAWAN BERDASARKAN DNA MITOKONDRIA - Hasra, Barratun Nisa; Idami, Zahratul; Manalu, Kartika (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Background: Genetic variation can share data on genetic diversity in fish populations. mtDNA is used to determine the kinship between grouper fish originating from TPI Gabion Medan Belawan. This study aims to obtain the latest genetic variations found in grouper populations (Epinephelus sp.), analyze for the kinship relationship between grouper populations (Epinephelus sp.), determine for the kinship relationship between grouper fish from TPI Gabion Medan Belawan and grouper fish that already exist in NCBI.Methods: This study used experimental methods.Results: The results of research on species of the genus Epinephelus namely Epinephelus fuscoguttatus, Epinephelus sexfasticus, and Epinephelus areolatus obtained by processing the sequencing data by analyzing nucleotide characters using the Mega 11 application. All three samples have low GC Content, it is said that all three samples have primitive properties. All three samples have the same genetic distance because they have a genetic distance value (Pairwise distance) below 3%.Conclusion: Reconstruction of phylogenetic trees shows that grouper kinship (phylogenetics) originating from TPI Gabion Medan Belawan with grouper fish that already exist in NCBI have close kinship and common ancestor